Factors associated with workers’ satisfaction with the mobile health check-up service of Queen Savang Vadhana Memorial Hospital - Kamsook, Nijsa; Kalampakorn, Surintorn; Kaewpan, Wonpen; Sillabutra, Jutatip (Journal of Public Health Nursing, 2024)
Mobile health check-up service is a service for annual health check-ups, risk-based health checks or periodic health checks for working age groups with the purpose to look for worker’s health problem. This cross-sectional study aimed to study the workers’ satisfaction with the mobile health check-up service of Queen Savang Vadhana Memorial Hospital. The sample comprised of 402 workers aged 18-60 years old, who received mobile health check-up service selected by simple random sampling for 5 companies receiving health examination during data collection period. Data were collected by using the online questionnaire which was examined for the content validity and reliability testing before data collections. The questionnaire consisted of questions assessing subjects’demographics, service quality, perceived service value, the prevention and control of the spread of COVID-19, worker’s satisfaction with the mobile health check-up service of Queen Savang Vadhana Memorial Hospital and repurchase intention. Data were analyzed by using the descriptive statistics, Chi-square test, Fisher’s Exact test and Multiple Logistic Regression Analysis. The study showed that overall of the workers’ satisfaction with the mobile health check-up service and the intentions of repurchase was at high level (M = 4.10 ± 0.36, M = 4.02 ± 0.57). Multiple logistic regression analysis indicated that the perceived service quality in tangible dimension (Adj. OR = 3.22, 95% CI= 1.05–9.90), the expected service quality in assurance dimension (Adj. OR = 9.88, 95% CI= 1.25-78.10) and empathy dimension (Adj. OR = 8.35, 95%CI = 1.19-58.80), perceived service value (Adj. OR= 2.58, 95%CI=1.06-6.25) and the prevention and control of the spread of COVID-19 in mobile health check-up (Adj. OR= 4.39, 95% CI= 1.99-9.65) were significantly related with the workers’ satisfaction with the mobile health check-up service of Queen Savang Vadhana Memorial Hospital. Findings suggest that the administrators should be established measures to ensure quality and standard of mobile health check-up service as relate to the vehicle segments, equipment and tools, and medical personnel. Measures to prevent and control the spread of COVID-19, which can make customer feel confident and satisfied in service should also be emphasized. In addition, the occupational health nurses should support and explain the necessity and benefits of health examinations to workers.